2003
DOI: 10.4049/jimmunol.171.2.1023
|View full text |Cite
|
Sign up to set email alerts
|

The RhoA Effector mDia Is Induced During T Cell Activation and Regulates Actin Polymerization and Cell Migration in T Lymphocytes

Abstract: Regulation of actin polymerization is critical for many different functions of T lymphocytes, including cell migration. Here we show that the RhoA effector mDia is induced in vitro in activated PBL and is highly expressed in vivo in diseased tissue-infiltrating activated lymphocytes. mDia localizes at the leading edge of polarized T lymphoblasts in an area immediately posterior to the leading lamella, in which its effector protein profilin is also concentrated. Overexpression of an activated mutant of mDia res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
58
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(61 citation statements)
references
References 47 publications
3
58
0
Order By: Relevance
“…Moreover, constitutively activated mDia1 (lacking the GTPase binding and a portion of the Dia inhibitory domain) enhanced actin accumulation while decreasing chemotactic migration upon TCR engagement (36). Indeed, activating mDia1 can also function to arrest the normally dynamic actin and microtubule cytoskeletons (34, 44 -46) and inhibit normal T cell function (36), consistent with our results. Collectively, these studies in addition to data presented here suggest that exquisite control of the dynamic actin cytoskeleton through actin nucleation-promoting factors is crucial for maintaining normal T cell function.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Moreover, constitutively activated mDia1 (lacking the GTPase binding and a portion of the Dia inhibitory domain) enhanced actin accumulation while decreasing chemotactic migration upon TCR engagement (36). Indeed, activating mDia1 can also function to arrest the normally dynamic actin and microtubule cytoskeletons (34, 44 -46) and inhibit normal T cell function (36), consistent with our results. Collectively, these studies in addition to data presented here suggest that exquisite control of the dynamic actin cytoskeleton through actin nucleation-promoting factors is crucial for maintaining normal T cell function.…”
Section: Discussionsupporting
confidence: 78%
“…Although p140mDia1 is a known RhoA effector, it is plausible that the disruption in adhesion and chemotactic migration is due to disruption of RhoA-mediated p140mDia1 activation and dysregulation of forminmediated actin dynamics. Indeed, a role for mDia1 and the related budding yeast formin Bni1 have been extensively characterized as promoting cell polarity and mediating both directional cell migration (33)(34)(35) and spontaneous cell migration (36). Furthermore, expression of constructs interfering with mDia1 function or small hairpin RNA constructs directed against mDia1 also disrupt microtubule organizing center reorientation in activated T cells, a hallmark of T cell polarization (36,37).…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with its role in actin polymerization in hair cells of the ear, naturally occurring mutations in mDia1 cause nonsyndromic deafness in humans (32). mDia1 was also recently found to be essential for mechanotransduction in response to integrin activation in SV-80 human fibroblast cells (33) but is not involved in the regulation of integrin-mediated cell adhesion in Jurkat cells (34). In conclusion, mDia1 appears to serve several basic cellular functions ranging from mechanosensation to cytokinesis through a possible effect on cytoskeletal organization.…”
mentioning
confidence: 90%
“…30,31 Furthermore it has been suggested that mDIA1 may suppress Rac1 activity in T cells but promote ROCK activation. 21 From recent work, it is becoming clear that different actin nucleators can work in thus the effect of C3 transferase on RhoA could have been stronger in this cell type.…”
Section: Coordinating Signaling At the Leading Edgementioning
confidence: 99%